Cross-Cultural Adaptation and Psychometric Evaluation of the Indonesian Version of the Utrecht Work Engagement Scale (UWES-9) - Findra Anugrah Putri Firdaus; Hillman Wirawan; Rizky Nur Fahrezi; Zahra Rizqi Quraini M. Zulkifli; Uswatun Hasanah Nurkholis (Har Press Indonesia, 2026)
This study aims to investigate a linguistic and cultural adaptation of the nine-item version of the Utrecht Work Engagement Scale (UWES-9) into Indonesian, as well as to examine its construct validity and internal reliability in the context of Indonesia. The adaptation process followed standard procedures for cross-cultural instrument adaptation, including forward translation, back-translation, field testing, and psychometric analysis. Data were collected from 252 workers in South Sulawesi Province with diverse demographic backgrounds and types of employment. Analysis was carried out using Confirmatory Factor Analysis (CFA) and internal reliability analysis. The results showed that two main dimensions of the UWES-9, namely vigor and dedication, had adequate construct validity and reliability, while the absorption dimension showed weaknesses in convergent validity and internal consistency (ω = .35). The three-factor model of the Indonesian version of the UWES-9 did not yet demonstrate optimal model fit (CFI = .83, TLI = .74, RMSEA = .22, SRMR = .09), indicating the need for structural modification, particularly in the absorption dimension. These findings highlight the importance of contextually and culturally valid instrument adaptation to ensure effective and accurate use before being widely applied for psychological measurement in Indonesian workplaces. In addition, further research is highly recommended to explore cultural factors that may influence individuals' responses to this instrument within the local work context.